2010
DOI: 10.1111/j.1750-2659.2010.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and other respiratory viruses in three Central American countries

Abstract: Please cite this paper as: Laguna‐Torres et al. (2011) Influenza and other respiratory viruses in three Central American countries. Influenza and Other Respiratory Viruses 5(2), 123–134. Background  Despite the disease burden imposed by respiratory diseases on children in Central America, there is a paucity of data describing the etiologic agents of the disease. Aims  To analyze viral etiologic agents associated with influenza‐like illness (ILI) in participants reporting to one outpatient health center, one pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 17 publications
(44 reference statements)
5
42
2
3
Order By: Relevance
“…Our data generally support the epidemiological features related to age and respiratory viral infections. Laguna-Torres et al (32) reported that RSV was the most common pathogen detected in children less than five years old in three countries. Further, RSV has a high prevalence, hospitalization, and mortality rates (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Our data generally support the epidemiological features related to age and respiratory viral infections. Laguna-Torres et al (32) reported that RSV was the most common pathogen detected in children less than five years old in three countries. Further, RSV has a high prevalence, hospitalization, and mortality rates (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Algunos de los estudios disponibles en la región proceden de Uruguay (12) y el sur de Brasil (13), donde la estacionalidad de los virus es diferente a la de los países del trópi-co como Colombia. Otros trabajos que han informado estacionalidad provienen de México y recientemente de Nicaragua, el Salvador y Honduras (14)(15)(16). En todos estos trabajos los patrones de estacionalidad de los virus respiratorios son diferentes, lo que justifica aún más el fortalecimiento de la vigilancia.…”
Section: Discussionunclassified
“…De manera similar este virus fue identificado en Italia como el segundo más frecuente después del VSR en las neumonías virales adquiridas en la comunidad en niños menores de 14 años (20). Por el contrario, este agente no fue común en la IRA viral de niños en México y Centroamérica (14,15), lo que probablemente esté relacionado con la capacidad diagnóstica de las pruebas utilizadas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Since its first description in 2001, hMPV has been detected in all continents independent of the economic status of different countries (1)(2)(3). The prevalence of hMPV in children with acute respiratory tract infection (ARTI) has been estimated as 5% to 15% (4), making it the 2nd or 3rd most prevalent pathogen in children with ARTI, with only human respiratory syncytial virus (hRSV) and possibly rhinovirus being more prevalent (5,6).…”
Section: Introductionmentioning
confidence: 99%